Fit to play? Health-related fitness levels of youth athletes: a pilot study - Pfeifer, C. E.; Sacko, R. S.; Ortaglia, A.; Monsma, E. V.; Beattie, P. F.; Goins, J.; Stodden, D. F. (The Journal of Strength and Conditioning Research, 2022)
A recent National Strength and Conditioning Association position statement suggests that many youth are not prepared for the physical demands of sport. The purpose of this study was to compare health-related fitness (HRF) of youth athletes with normative findings from the general population. We recruited 136 athletes (63 male and 73 female athletes) aged 11-19 (16.01 ± 1.35) years and collected HRF (body composition, cardiorespiratory endurance, musculoskeletal strength and endurance). Results were categorized based on FITNESSGRAM® standards and compared with Canadian youth general population normative data. Most male athletes were classified as "needs improvement" for cardiorespiratory and muscular endurance, and body mass index (BMI). Conversely, most female athletes were at or above the "healthy fitness zone" for all measures. Male athletes at both age groups (11-14, 15-19; p < 0.001) and female athletes aged 11-14 (p < 0.05) demonstrated lower cardiorespiratory endurance compared with Canadian general population. Female athletes (both age groups) demonstrated greater muscular strength, and male athletes (age, 15-19 years) demonstrated lower BMI than the Canadian general population. The results are concerning as male athletes demonstrated poorer HRF compared with the general population. Although most female athletes were within healthy ranges, a portion of them were still at risk. Considering the demands sport places on the body, evaluating HRF is paramount for performance and injury prevention but more importantly for overall health. Youth sport and strength coaches should evaluate and aim to enhance HRF, as participation in sport does not guarantee adequate HRF. Promoting long-term athletic development and life-long health should be a priority in youth.